(NqZYK PTIC(B: [(NpO\MA(B] / s (N~ASTX (B8s - (NnAWOI(B, (NaLI[ERs ((NtA[KENT(B: s (NfAN(B, s, 1970)
(Nw WOSXMOJ TOM UZBEKSKOGO PO\TA(B, (NMYSLITELQ I GOSUDARSTWENNOGO DEQTELQ aLI[ERA nAWOI (B(1441 - 1501) (NWO[LO PROIZWEDENIE (B"(NqZYK PTIC(B", (NNAPISANNOE POD WLIQNIEM PO\MY (B"(NrE^I PTIC(B" (NIZWESTNOGO PERSO(B-(NTADVIKSKOGO PO\TA fARIDUDDINA aTTARA(B.s
rus
Keywords: (NpO\MAs; (NsTIHOTWORENIQs